Physiological and biochemical measurements on juvenile Antarctic rockcod (Trematomus bernacchii) from McMurdo Sound - Miller, Nathan; Todgham, Anne; Davis, Brittany; Flynn, Erin (IEDA: US Antarctic Program Data Center, 2017)
Abstract: This dataset includes data from the publication "Davis, et al. (2016) - Juvenile Antarctic rockcod (Trematomus bernacchii) are physiologically robust to CO2-acidified seawater". Included are data on cardiorespiratory physiology, survival, metabolic rate, metabolic enzyme activity (citrate synthase) and seawater chemistry.